Manobo dictionary of Manobo as spoken in the Agusan river valley and the Diwata mountain range - Gelacio, Teofilo E. (Urios College, 2000)
A compilation of Manobo words including pronunciations, spellings, abbreviations and English translations to help younger generations of Manobo take pride in their language and culture and preserve the language by learning how to speak Manobo.